Analysis of phenanthrene degradation by Ascomycota fungi isolated from contaminated soil from Reynosa, Mexico. (1st May 2021) - de la Cruz‐Izquierdo, R.I.; Paz‐González, A.D.; Reyes‐Espinosa, F.; Vazquez‐Jimenez, L.K.; Salinas‐Sandoval, M.; González‐Domínguez, M.I.; Rivera, G.
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are organic compounds generated mainly by anthropogenic sources. They are considered toxic to mammals, since they have carcinogenic, mutagenic and genotoxic properties, among others. Although mycoremediation is an efficient, economical and eco‐friendly technique for degrading PAHs, the fungal degradation potential of the phylum Ascomycota has not been widely studied. In this work, we evaluated different fungal strains from the polluted soil of 'La Escondida' lagoon in Reynosa, Mexico to know their potential to degrade phenanthrene (PHE). Forty‐three soil isolates with the capacity to grow in the presence of PHE (0·1% w/v) were obtained. The fungi Aspergillus oryzae MF13 and Aspergillus flavipes QCS12 had the best potential to degrade PHE. Both fungi germinated and grew at PHE concentrations of up to 5000 mg l −1 and degraded 235 mg l −1 of PHE in 28 days, with and without an additional carbon source. These characteristics indicate that A. oryzae MF13 and A. flavipes QCS12 could be promising organisms for the remediation of sites contaminated with PAHs and detoxification of recalcitrant xenobiotics.